TESTOSTERONE SUPPLEMENTATION AND RETINAL VASCULAR DISEASE. Issue 11 (November 2018) - Dedania, Vaidehi S.; Zacks, David N.; Pan, Wei; VanderBeek, Brian L.
Abstract : Purpose: To determine whether testosterone supplementation is associated with retinal artery occlusion (RAO) or retinal vein occlusion (RVO). Methods: Retrospective matched cohort study using data from a large national U.S. insurance database. The testosterone cohort consisted of all male patients who filled a prescription for testosterone from 2000 to 2013. Five controls were matched on age (±3 years), sex, race, and similar time in plan (±3 months) for every exposed patient. Exclusion occurred for <2 years in the plan, <1 eye care visit, medications known to affect androgen levels, and systemic diseases associated with occlusions or increased testosterone. Cox proportional hazard regression assessed the hazard of a new diagnosis of RAO or RVO while controlling for age, race, diabetes mellitus, and hypertension. Results: A total of 35, 784 incident testosterone users were compared with 178, 860 matched controls. Ninety-three (0.3%) RAOs and 50 (0.1%) RVOs were found in the testosterone cohort and contrasted with 316 (0.2%) RAOs and 232 (0.1%) RVOs in the control group. After multivariate analysis, testosterone supplementation significantly increased the hazard of RAO (hazard ratio: 1.43, 95% confidence interval: 1.12–1.81, P = 0.004), but not of RVO (hazard ratio: 1.03, 95% confidence interval: 0.74–1.42, P = 0.86). Conclusion: Although the incidence of RAO and RVO is low in users of testosterone, supplementation therapy is associated with an increased hazard of RAO, but apparently not of RVO. Abstract : Supplemental Digital Content is Available in the Text.This is a study that evaluated for an association between testosterone supplementation and retinal vascular occlusions, which found a significantly increased hazard for developing retinal arterial occlusion with exogenous testosterone use.